Enhancing Students’ Motivation in English Learning through Deep Learning, Teacher Self-Efficacy, and AI-Based Instruction - Santi Fira Novia; Djoko Sutrisno; Tengku Intan Suzila Tengku Sharif (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aimed to explore the integration of a deep learning-based pedagogical approach, teacher self-efficacy, and AI-based instructional media in enhancing students’ motivation in learning English at SMA Muhammadiyah 1 Temanggung. The study investigated how innovative teaching approaches, teachers’ confidence in their instructional abilities, and the integration of artificial intelligence in classroom practices contribute to creating a more engaging, interactive, and student-centered learning environment. The topic was considered important because students’ motivation has become a major challenge in English language learning, particularly in technology-mediated classrooms and non-urban educational settings where learning resources and instructional innovation may still be limited. This research employed a qualitative approach, data were collected through interviews, classroom observations, and focus group discussions involving English teachers and students at SMA Muhammadiyah 1 Temanggung. The collected data were analysed thematically to identify recurring patterns, meanings, and experiences related to students’ motivation in learning English. This study was expected to contribute to the development of more effective, student-centered, and technology-enhanced instructional practices in English language teaching. The findings of this study were also expected to support teachers and educational institutions in developing more adaptive and motivating learning environments for students in the digital era.